Freedom as Prevention: Mechanisms of Autonomy Support for Promoting HIV Pre-Exposure Prophylaxis Use and Condom Use among Black MSM in 3 US Cities—HPTN 073 - Nelson, LaRon E.; Boyd, Donte T.; Beauchamp, Geetha; Emel, Lynda; Wilton, Leo; Whitfield, Darren; Ramos, S. Raquel; Ajiboye, Wale; Hill, Mandy J.; Conserve, Donaldson F.; Thomas, Portia; Hightow-Weidman, Lisa; et al. (Journal of Urban Health, 2022)
Healthcare providers who use controlling or coercive strategies may compel short-term enactment of HIV and sexually transmitted infection prevention behaviors but may inadvertently undermine their client’s motivation to maintain those behaviors in the absence of external pressure. Autonomous motivation refers to the self-emanating and self-determined drive for engaging in health behaviors. It is associated with long-term maintenance of health behaviors. We used structural equation modeling to investigate whether autonomy support was associated with increased odds of therapeutic serum levels of pre-exposure prophylaxis, through a pathway that satisfies basic psychological needs for autonomous self-regulation and competence regarding pre-exposure prophylaxis use. We also investigated whether autonomy support was associated with decreased odds of condomless anal intercourse via the same psychological needs-satisfaction pathway of autonomous self-regulation and competence regarding condom use. We tested these two theorized pathways using secondary data from a longitudinal sample of Black men who have sex with men from across three cities in the US ( N = 226). Data from the sample fit the theorized models regarding the pathways by which autonomy support leads to the presence of therapeutic PrEP levels in serum ( χ 2 = 0.56; RMSEA = 0.04; CFI = .99, TLI = 0.98) and how it also leads to decreased odds of condomless anal intercourse ( χ 2 = 0.58; RMSEA = 0.03; CFI = 0.99; TLI = 0.98). These findings provide scientific evidence for the utility of self-determination theory as a model to guide intervention approaches to optimize the implementation and impact of PrEP for Black men who have sex with men.